Prognostic values of the gross volume of metastatic lymph nodes in patients with esophageal squamous cell carcinoma treated with definitive concurrent chemoradiotherapy - Li, Yang; Li, Yanqi; Huang, Hui; Guo, Zhoubo; Zhang, Kunning; Zhang, Wencheng; Pang, Qingsong; Wang, Ping (Frontiers in Oncology, 2022)
Purpose We aim to explore whether the gross volume of metastatic lymph nodes (GTVnd) and the gross volume of primary tumor (GTVp) could be prognostic factors for esophageal squamous cell carcinoma (ESCC) patients treated with definitive concurrent chemoradiotherapy (dCCRT). Methods We retrospectively analyzed 252 ESCC patients treated with dCCRT in the era of intensity-modulated radiation therapy (IMRT) at our institution. The cut-off value for the GTVnd derived from the restricted cubic splines (RCS) was determined. Univariate and multivariate Cox proportional hazard models were performed to determine the association between GTVnd and prognosis. we performed recursive partitioning analysis (RPA) method using GTVnd to develop a new risk stratification (TGTVndM). Moreover, the linear trend χ2, likelihood ratio χ2, and akaike information criterion (AIC) were used to determine the prognostic value between the TNM and TGTVndM staging systems. Results The five-year overall survival (OS) rate was 30.6%, with a median follow-up of 38 months. The cut-off value of GTVnd determined by the RCS was 4.35 cm3. GTVnd≥4.35 cm3 was an independent and significant negative prognostic factor for OS (HR=1.949, P<0.001), progression free survival (PFS) (HR=1.425, P=0.048), and distance metastasis free survival (DMFS) (HR=2.548, P=0.001). In multivariable analysis, gender, clinical T stage, and GTVnd were independently associated with OS. RPA segregated patients into 3 prognostic groups: high risk (T1-4 GTVnd≥4.35, n=126, III stage) , intermediate risk (T4 GTVnd<4.35,n=38,II stage), and low risk(T1-3GTVnd＜4.35, n=88, I stage). The 5-year OS(P<0.001), PFS (P=0.002), and DMFS (P=0.001) were significantly worse in high-risk group in comparison with the intermediate and low risk groups. Compared with the TNM staging system, the clinical T stage combined with GTVnd (TGTVndM) had a higher linear trend χ2 (26.38 versus 25.77), higher likelihood ratio χ2 (24.39 versus 20.69), and lower AIC (1255.07 versus 1260.06). Conclusions GTVnd may serve as a good prognostic factor in predicting distant metastasis and death for ESCC patients treated with dCCRT. The TGTVndM staging system demonstrated superior accuracy for predicting OS and could serve as a more effective prognostic guidance for unresectable ESCC patients.